Evaluation of the therapeutic efficacy of hridayamohini in the management of respiratory tract infections based on clinical and laboratory data from previous case records - Brahmadathan U; K Jagannathan; B Rajkumar; Shabel P V; Narayana Prasad R; Aneesh S Murukan; Hemand Aravind; Anisree P A; Anjana Krishnan (Indian Journal of Integrative Medicine, 2023)
Respiratory tract infections have been a major health concern since time immemorial, owing to their high potential for spread across a larger population, causing mild to severe morbidity and even death. Many classical and proven formulations have been in use for many generations in India’s traditional medical systems, particularly the Siddha System of Medicine. Although new pathogens emerge all the time, these formulations have clearly demonstrated their potential in the past in slowing the spread of various epidemics such as chikungunya and dengue by assisting the body in fighting the infection and generating herd immunity. Based on clinical and laboratory findings, a proprietary Siddha medicine named Hridayamohini, developed based on such classically proven Siddha formulations, was evaluated through this evaluation. The medicine was found to have significant expectorant, antitussive, decongestant, anti-inflammatory, platelet stimulating, and anti-allergic potentials after a two-week evaluation period.